(untitled) (Journal of Universal Science Research, 2023)
Uterine erosion - of the mucous membrane of the cervix damage Violation of the normal state of the mucous membrane can be caused by physical and chemical factors. In some cases, the uterus in childless women the cause of erosion of the neck may be an anomaly in the development of the epithelium. Taking into account the nature of the origin, the disease is a real erosion and pseudo-erosion (ectopia) is divided into types